Perancangan Dan Analisis Topologi Jaringan Pada BPJS Ketenagakerjaan Cabang Palembang Menggunakan Cisco Packet Tracer - Gunawan Gunawan; Jemakmun Jemakmun (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The stability of computer network infrastructure is a critical factor in supporting public service operations, including at the BPJS Ketenagakerjaan Palembang Branch Office, which serves four divisions across two floors with a total of 37 Personal Computers (PCs). This study aims to design and analyze a Local Area Network (LAN) topology based on the Extended Star topology combined with a Class C IPv4 addressing scheme (192.168.1.0/24), and to evaluate its fault tolerance characteristics through simulation using Cisco Packet Tracer. The method includes field observation, simulation experiments, and literature study, with two testing scenarios: normal operating conditions and backbone link-failure conditions. Results under normal conditions show a 100% ICMP packet delivery success rate (0% packet loss) with an average Round Trip Time (RTT) of 5 ms. However, under the backbone failure scenario, the network experienced total communication failure with 100% packet loss, confirming the vulnerability of a pure Star architecture to a single point of failure. Based on these findings, this study recommends a Hybrid Star-Ring architecture, combining an Extended Star topology at the client level with a Spanning Tree Protocol (STP)-based Backbone Ring at the main switch interconnection, together with VLAN, Port Security, Access Control List (ACL), and Quality of Service (QoS) to enhance security and service quality in real-world deployment.